2010
DOI: 10.1890/08-0611.1
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing the agronomic yield gap with improved nitrogen use efficiency: a modeling approach

Abstract: Improving nitrogen use efficiency (NUE) in the major cereals is critical for more sustainable nitrogen use in high-input agriculture, but our understanding of the potential for NUE improvement is limited by a paucity of reliable on-farm measurements. Limited on-farm data suggest that agronomic NUE (AE(N)) is lower and more variable than data from trials conducted at research stations, on which much of our understanding of AE(N) has been built. The purpose of this study was to determine the magnitude and causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Based on the study in Yaqui Valley in Mexico, Ahrens et al [224] indicated that the yield gap in wheat could be minimized by improving nitrogen use efficiency (NUE). According to them, split applications of N fertilizer significantly increased seed yield and profit, and reduced N pollution.…”
Section: Focus On Both Boosting Crop Productivity and Improving Ecosymentioning
confidence: 99%
“…Based on the study in Yaqui Valley in Mexico, Ahrens et al [224] indicated that the yield gap in wheat could be minimized by improving nitrogen use efficiency (NUE). According to them, split applications of N fertilizer significantly increased seed yield and profit, and reduced N pollution.…”
Section: Focus On Both Boosting Crop Productivity and Improving Ecosymentioning
confidence: 99%
“…For example, developing sitespecific management zones for N on the basis of yield history, aerial photographs of soil color, soil sampling, topography, and farmer experiences has been shown to increase yields significantly without a concomitant increase in the rates of N application. 10 Better synchronizing N supply and demand in smallholder systems would meet all Climate Smart Agriculture objectives-less excess N could reduce nitrous oxide emissions, one of the most important agricultural greenhouse gases; more targeted N application could increase yields; and reducing farmer N costs via more efficient application techniques would increase both net income and resilience to various shocks, including spikes in fertilizer price. 10 Precision Agriculture for Smallholders To date, PA approaches have been predominantly adopted in large-scale, industrial systems in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…10 Better synchronizing N supply and demand in smallholder systems would meet all Climate Smart Agriculture objectives-less excess N could reduce nitrous oxide emissions, one of the most important agricultural greenhouse gases; more targeted N application could increase yields; and reducing farmer N costs via more efficient application techniques would increase both net income and resilience to various shocks, including spikes in fertilizer price. 10 Precision Agriculture for Smallholders To date, PA approaches have been predominantly adopted in large-scale, industrial systems in developed countries. Uptake in developing countries is low and, as in developed countries, concentrated in large-scale systems with high-value crops.…”
Section: Introductionmentioning
confidence: 99%
“…These production increases need to occur despite multiple interacting challenges such as the need to adapt to a rapidly changing climate, increased competition for agricultural land from other land uses, and societal demands for environmental stewardship (Godfray et al 2010, Lambin and Meyfroidt 2011, Vermeulen et al 2012. With limited opportunities for the expansion of agricultural land, and with vigilance against local environmental impacts (Licker et al 2010, Bommarco et al 2013, intensification and improvement in resource use efficiency have been identified as two of the most prospective ways to increase agricultural production (Green et al 2005, Ahrens et al 2010, Phalan et al 2011, Tilman et al 2011. Yield gaps-where farms produce less than the maximum currently attainable under ideal management (Mueller et al 2012, van Ittersum et al 2013)-often occur in practice, and closing this gap through the intensification of agricultural management is a global priority for addressing future food security (Neumann et al 2010, Mueller et al 2012.…”
Section: Introductionmentioning
confidence: 99%